GS-9669: a novel non-nucleoside inhibitor of viral polymerase for the treatment of hepatitis C virus infection. Issue 10 (October 2014) - Gentile, Ivan; Buonomo, Antonio Riccardo; Zappulo, Emanuela; Coppola, Nicola; Borgia, Guglielmo
Abstract : Hepatitis C virus (HCV) is an RNA virus that chronically infects 2–3% of the world's population. About 25% of these chronic carriers evolve towards liver cirrhosis, a disease that is significantly associated with reduced survival and quality of life. Antiviral therapy can eradicate the infection − a process that is associated with a reduced disease progression rate. Several oral direct agents have been developed and tested for the treatment of HCV infection. This review focuses on the mechanism of action, pharmacokinetics, efficacy, safety and resistance of GS-9669, a non-nucleoside inhibitor of viral polymerase, active against HCV genotype 1. In combination with other oral antivirals, GS-9669 results: in very high rates of viral eradication (90–100%) in patients with HCV genotype 1 infection, with a good tolerability and safety profile. In conclusion, GS-9669 is a good candidate to be used in interferon-free combinations for the treatment of chronic HCV infection.